STUDY ON THE PROPERTIES OF A NEW IRRIGANT USED IN THE ENDODONTIC THERAPY FALLOWED BY PROSTHETIC RESTORATIVE TREATMENT - A LITERATURE REVIEW- - Liana Aminov; Mihaela Salceanu; Yllka Decolli; Cristina Antohi; Lupu Iulian Costin; Ovidiu Stamatin; Laura Elisabeta Checherita (Romanian Dental Association for Education, 2019)
The purpose of endodontic therapy is the most judicious decontamination of the endodontic space and its subsequent sealing through a tight filling of the canal. In this sense, obtaining the permeability of the root canal system is essential. Of the irrigating solutions valid for endodontic use can be mentioned: NaOCl, EDTA, chlorhexidine, potassium iodide (IKI). However, none of these irrigants meet the ideal requirements, each having the advantages and disadvantages of their own. Materials and method: A number of 34 articles ranged from 2003 to 2015 were analyzed, in view to assess the cleanning effect and the antibacterial properties of the MTAD, the newer irrigant used in the chemomechanical endodontic treatment. Conclusions: The studies have demonstrated the efficacy of MTAD as an antimicrobial agent, being very effective in removing the smear layer from the instrumented canal walls and favoring further adhesive restorative and prosthetic procedures.